2007
DOI: 10.1242/jcs.03322
|View full text |Cite
|
Sign up to set email alerts
|

Cdc2-mediated Schwann cell migration during peripheral nerve regeneration

Abstract: Schwann cell migration facilitates peripheral nerve regeneration after injury. We have recently found increased activation of Cdc2 kinase in regenerating sciatic nerves. Here we show that Cdc2 phosphorylation of caldesmon regulates Schwann cell migration and nerve regeneration. A robust but transient increase in Cdc2 expression was found in cultured Schwann cells prepared from the sciatic nerve in rats that had undergone crush injury for 7 days. These `injury-preconditioned' Schwann cells exhibited enhanced mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…There is evidence demonstrating that Cdc2 is expressed in astrocytes after SCI (unpublished data). As has been implicated by Cdc2-mediated migration of Schwann cells and cancer cells (13,45), locally upregulated Cdc2 activity by SMS in non-neuronal cells (e.g., astrocytes) could promote their migration into the injury cavity as observed by the increased number of Hoechststained nuclei by SMS treatment. Cells that migrated into the injury cavity could be involved in trabecula formation and contribute to axonal regeneration.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…There is evidence demonstrating that Cdc2 is expressed in astrocytes after SCI (unpublished data). As has been implicated by Cdc2-mediated migration of Schwann cells and cancer cells (13,45), locally upregulated Cdc2 activity by SMS in non-neuronal cells (e.g., astrocytes) could promote their migration into the injury cavity as observed by the increased number of Hoechststained nuclei by SMS treatment. Cells that migrated into the injury cavity could be involved in trabecula formation and contribute to axonal regeneration.…”
Section: Discussionmentioning
confidence: 86%
“…We have recently found that Erk1/2 and Cdc2 pathways are activated during axonal regeneration in peripheral sciatic nerves (9,13). Here, regulation of phospho-Erk1/ 2 and Cdc2 proteins by SMS treatment was investigated in the dorsal spinal cord and in the motor cortex where the cell bodies of CST axons are located.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations